Molecular weight distribution of raw and catalytic fast pyrolysis oils: comparison of analytical methodologies. Issue 7 (22nd January 2020) - Harman-Ware, Anne E.; Orton, Kellene; Deng, Chris; Kenrick, Sophia; Carpenter, Daniel; Ferrell, Jack R.
Abstract : Comprehensive analysis of the molecular weight distribution of raw and catalytic fast pyrolysis oils remains a key technical hurdle to understanding oil quality and multiple methods may be necessary to accurately represent all components present. Abstract : Comprehensive analysis of the molecular weight distribution of raw and catalytic fast pyrolysis oils derived from biomass remains a key technical hurdle to understanding oil quality as it relates to downstream use and multiple methods may be necessary to accurately represent all components present. Here, we report the molecular weight distribution metrics of fast pyrolysis (FP) and catalytic fast pyrolysis (CFP) oils as determined by gel permeation chromatography (GPC) combined with UV-diode array (UV), differential refractive index (RI), and multi-angle laser light scattering (MALS) detection. The measured molar mass distributions revealed that FP oil consisted of a higher proportion of larger products relative to the low molecular weight products contained in the CFP oil. GPC/RI and UV methods showed FP oil to have higher weight-average molecular weight ( M w ) and number-average molecular weight ( M n ) than CFP oil based on elution time. However, GPC/MALS, determined the two oils to have similar overall molecular weight distribution metrics ( M w and M n ) and yielded values significantly higher than those determined by RI and UV detectors relative to external standards. Overall, the use of a multiple detection GPC method could enable a more accurate comparison and determination of true molecular weight metrics of bio-oils.